Pedagodzy społeczni jako współtowarzysze migrantów w procesie adaptacji społeczno-kulturowej, integracji i inkluzji - Pietrusińska, Marta (Kultura-Społeczeństwo-Edukacja, 2020)
Increased migration to Poland and at the same time an increase in anti-immigrant attitudes cause that social pedagoguesface a new challenge related to the integration and inclusion of migrants. In the article I focus on a transformation of social pedagogues roles due to the mentioned above social changes and new challenges – the discourse the introduces symbolic violence, learned helplessness and lack of agency of migrants, and the insufficient number of social pedagogues with intercultural and andragogical competence. Based on these difficulties faced by social pedagogues I describe what could be their role in the process of integration of migrants and the host society.